KONFIGURASI INTER-VLAN PADA CISCO BERBASIS GRAPHICS USER INTERFACE (GUI) SEBAGAI PEMBELAJARAN PERALATAN JARINGAN KOMPUTER CISCO - Pratama, Aditya Wisnu; Wintolo, Hero; Astuti, Yenni (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
Computer network using LAN has limitations in terms of the large number of computers that will be connected to the switch equipment. This limitation can be overcome by connecting the LAN between each other using a router. Networks inter LAN still pose a problem in terms of safety, although the amount can be overcome. To overcome the problem requires a LAN in a small group that is often known as Virtual Local Area Network (VLAN). VLAN can be connected as is often done on the LAN in general with the addition of some equipment that is able to be used as the connecting or known by the name of inter-VLAN. inter-VLAN configuration can be done directly and indirectly. the configuration directly by configuring the network equipment such as switches and routers, while the indirect configuration can be done using packet tracer. In doing inter-VLAN configuration requires a command performed by an administrator. Commands that is configured on the network equipment is a command that is still a command line or a particular script. For people who have not worked as a network administrator needed a software Graphics User Interface (GUI) for ease in studying network administration. Software Graphics User Interface (GUI) can facilitate a person who has worked as an administrator to configure inter-VLAN.